Lives for older people in the context of Covid-19 - Koeche, Cristiane (2023)
Objective: Investigate the lives made available on the social networks of institutions and professional advice about people going to s in the face of Covid-19 to verify which institutions most disseminated these lives which was the most used social network and which professional had more participations. Method: A retrospective, exploratory, descriptive and infometric study was conducted. Results: Three institutions, SBGG, FNILPI and ABG – directly related to elderly  – disseminated lives aimed at this population or at caregivers and family members;  among the professionals who had the most participation  in the lives were geriatric doctors, the largest number of access was given to the live entitled "Covid-19 Pandemic", which was held in June by a geriatrician, and which had 7.829 accesses, being disclosed in the YT of SBGG.  SBGG was the institution that most disseminated lives, the most used social network was IG, and July was the month with the highest number of disclosures. Conclusion: There is a lack of attention and care for the elderly.